III–V/Silicon Hybrid Non-linear Nanophotonics in the Context of On-Chip Optical Signal Processing and Analog Computing - Constans, Léa; Combrié, Sylvain; Checoury, Xavier; Beaudoin, Grégoire; Sagnes, Isabelle; Raineri, Fabrice; de Rossi, Alfredo (Frontiers in Physics, 2019)
We discuss the application of silicon hybrid photonic integration technology for all-optical signal processing. The core is a photonic crystal nanocavity made of a III–V semiconductor alloy. This ensures ultra-fast and energy-efficient all-optical operation, which is crucial for scaling from a single device to a non-linear photonic processor where ideally a large number of non-linear elements cooperate. We discuss all-optical sampling as an immediate application of this technology and give an example of a future non-linear integrated circuit based on this technology.